Exploring and Exploiting the Dynamics of Networks in Complex Applied Research Projects: A Reflection on Learning in Action. (28th February 2021) - Coughlan, Paul; Coghlan, David; Rigg, Clare; O'Leary, Denise
Abstract: Since 1984, the European Union (EU) has supported research and development activities covering almost all scientific disciplines through a series of multi‐annual Framework Programmes. The current programme is Horizon 2020. Common across the key indicators of research project performance have been actions by companies, including introduce and test innovations new to the company or the market. Initiatives to achieve these objectives require researchers to generate transdisciplinary knowledge in partnership with practitioners as co‐researchers. This paper reflects on the authors' experience of engaging in five EU‐funded complex applied research projects over 20 years. The paper locates the process of the five projects in network action learning and Mode 2 knowledge production. It offers a theoretical framework expressed in three hypotheses to guide those who design and implement projects, those who approve and provide funding, and those who exploit and build upon the resulting research.